2022
DOI: 10.1155/2022/9228910
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Students’ Test Preparation Strategies and Test Anxiety: Gender, Age, and Parents’ Level of Education as Control Variables

Abstract: Although students’ test preparation tendencies are related to their test-taking confidence, empirical evidence on how students’ test preparation strategies relate to their test anxiety is still lacking. Framed within the skills deficit model, we examined the associations between students’ test preparation strategies (cognitive, metacognitive, and social preparation strategies) and their test anxiety (worry, cognitive, tension, and physiological test anxiety). Students’ gender, age, and parents’ level of educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Thus, individuals who use psychoactive substances are likely less prepared for the assessment of learning outcomes than their peers who do not. Nwosu et al (2022) observed that students who are more confident in their test-taking abilities due to their preparedness experience less test anxiety. Misuse of stimulants by college students has also been associated with increased deficits in executive functions (Edinoff et al, 2022) suggesting they may have trouble with cognitive flexibility and self-monitoring, planning and following it through to goal attainment, exhibiting inhibition and updating of working memory, and managing emotions, all of which are vital for academic success (Austin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, individuals who use psychoactive substances are likely less prepared for the assessment of learning outcomes than their peers who do not. Nwosu et al (2022) observed that students who are more confident in their test-taking abilities due to their preparedness experience less test anxiety. Misuse of stimulants by college students has also been associated with increased deficits in executive functions (Edinoff et al, 2022) suggesting they may have trouble with cognitive flexibility and self-monitoring, planning and following it through to goal attainment, exhibiting inhibition and updating of working memory, and managing emotions, all of which are vital for academic success (Austin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%